GAMBARAN LINGKUNGAN KERJA, KOMUNIKASI KERJA DAN SEMANGAT KERJA PERAWAT RUMAH SAKIT UMUM PARU Dr. H.A. ROTINSULU BANDUNG - Kamal, Nasrul; Sumiyati, Sumiyati; Purnama, Ridwan (Journal of Business Management Education (JBME), 2018)
Purpose - The purpose of this study is to see the description of work environment, work communication and moraleDesign/methodology/approachh - The design of this study was cross sectional method. This research uses descriptive approach with explanatory survey method. The nurses analysis unit is 107 people. Data collection using questionnaire. The analysis technique used is descriptive technique by using frequency distributionFindings - Based on the results of the research using descriptive analysis, the results obtained that work environment in the conducive category, wprk communication in the good category, and morale in the high category. Originality/value -Â  The differences in this study located on an object research , time research , a measuring instrument , literature that used , the theory that is used and the results of the study.